Ergonomics tips for working / Intan Syaherra Ramli - Ramli, Intan Syaherra (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2020)
Working online either at the office or home is a new norm nowadays due to the pandemic Covid-19. Even though our country now is in the recovery phase, we must take the precautions by following the standard of operating procedure (SOP) when handling our daily task. In education field, most of the academician have to conduct their classes online.